Technical and Vocational Education in Malaysia - Ab Ghani, Mohd Ruddin; Abdullah, Abu (2002)
In Malaysia, technical and vocational education is accorded a high priority in nation's industrialization agenda. With the vision of becoming an industrialized nation in 2020, Malaysia must prepare a well-educated, skilled and competitive workforce. Thus, the government has placed human resource development as a major emphasis and a strategic policy to enhance Malaysia's competitive edge over other developing countries. In the era of globalization and K-economy, the future of Malaysia's competitiveness depends on the skills of its workforce. The impact of globalization and K-economy has led to a heightened awareness of the need to develop a competent, disciplined and highly skilled labor force with strong ethical and moral values and commitment to excellence.